Analysis Of The Implementation Of The Policy For Controlling Illegal Buildings By The Kuningan Regency Civil Service Police Unit - Kadek Ransyastiti Pertiwi; Djohermansyah Djohan; Rizari Rizari (Jurnal Scientia, 2024)
This research is motivated by the large number of illegal buildings (buildings without permits) that occur in Kuningan District, Kuningan Regency. The aim of the research is to analyze and determine the implementation of the illegal building control policy by the Kuningan Regency Civil Service Police Unit. Then use descriptive qualitative methods. The data sources used are primary data and secondary data. Data collection techniques through observation, interviews and documentation. Data analysis method using data reduction, data presentation and drawing conclusions. The results of this research show thatimplementation of the policy for controlling illegal buildings in Kuningan District by the Kuningan Regency Civil Service Police Unit. In terms of communication indicators, the Kuningan Regency Civil Service Police Unit is still not optimal, this is proven based on research results that the communication carried out is not consistent with controlling illegal buildings. The resource indicator is still inadequate, this is proven based on data on the number of officers from the Kuningan Regency Civil Service Police Unit. The disposition and bureaucratic structure indicators have been implemented quite well, as evidenced by the results of research related to the implementation of controlling illegal buildings in Kuningan District. The inhibiting factor in implementing the policy to control illegal buildings in Kuningan District by the Kuningan Regency Civil Service Police Unit is the limited number of human resources and budget allocation. Efforts made to overcome the inhibiting factors for the Kuningan Regency Civil Service Police Unit in carrying out control of illegal buildings in Kuningan District, namelyAdding apparatus resources and increasing their competence and increasing the budget inKuningan Regency Civil Service Police Unit in carrying out control over illegal buildings.